Construction of ZnII/CdII-based MOFs containing a tripodal aromatic carboxylate ligand with unequal arms and their fluorescence detection for Cu2+ and Fe3+ cations. Issue 8 (6th February 2023) - Huang, Gui-Mei; Li, Shuang; Ma, Meng-Xia; Li, Shi-Ming; Li, Wen-Qiang; Ni, Qing-Ling; Gui, Liu-Cheng; Wang, Xiu-Jian
Abstract : Four MOFs have been synthesized and characterized. The luminescent sensing investigation indicates that compound 1 exhibits extremely sensitive and selective detection of Cu 2+ and compounds 2–4 show extremely sensitive and selective detection of Fe 3+ . Abstract : Four MOFs with mixed ligands, [Zn3 (3-BABA)2 (bpa)2 (H2 O)2 ] n (1 ), [Cd3 (3-BABA)2 (bpa)2 ] n (2 ), [Cd3 (3-BABA)2 (bpe)2 ] n (3 ), and {[Cd3 (3-BABA)2 (bib)(DMA)2 ]·H2 O} n (4 ) (where 3-H3 BABA = 4′, 4′′′-(((2-carboxyphenyl)azanediyl)bis(methylene))bis(([1, 1′-biphenyl]-2-carboxylic acid)), bpa = 4, 4′-azopyridine, bpe = 1, 2-bis(pyridin-4-yl)ethane, and bib = 1, 4-bis(imidazole)butane), have been synthesized. They are characterized by single crystal X-ray diffraction, X-ray powder diffraction (XRPD), thermogravimetric analysis (TGA) and Fourier transform infrared (FT-IR) spectroscopy. In 1, two 3-BABA and two bpa bridge three Zn 2+ ions to form a bicyclic [Zn3 (3-BABA)2 (bpa)2 ] unit which is further bridged by carboxylate groups with its adjacent units, resulting in a one-dimensional chain. In 2, 3 and 4, the [Cd3 (CO2 )6 ] units are bridged by six 3-BABA ligands into a three-dimensional structure. However, the adjacent [Cd3 (CO2 )6 ] units in 2 and 3 are doubly-bridged simultaneously by corresponding pyridyl ligands, while the adjacent [Cd3 (CO2 )6 ] units in 4 are singly-bridged simultaneously by corresponding pyridyl ligands. The luminescence sensing investigation indicates that compound 1 exhibits extremely sensitive and selective detection of Cu 2+ with a detection limit of 0.363 μM, and compounds 2–4 show extremely sensitive and selective detection of Fe 3+ with detection limits of 0.539 μM, 0.265 μM, and 0.748 μM, respectively. Competitive experiments in the presence of interfering cations with 1–4 revealed no major change in the quenching efficiency.